2020
DOI: 10.3390/jcm9082455
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes and Risk Factors of Renal Failure Requiring Dialysis after Heart Transplantation: A Nationwide Cohort Study

Abstract: Acute kidney injury and renal failure are common after heart transplantation. We retrospectively reviewed a national cohort and identified 1129 heart transplant patients. Patients receiving renal replacement therapy after heart transplantation were grouped into the dialysis cohort. The long-term survival and risk factors of dialysis were investigated. Patients who had undergone dialysis were stratified to early or late dialysis for subgroup analysis. The mean follow-up was five years, the incidence of dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
2
9
0
2
Order By: Relevance
“…AKI, especially AKI-D, is common and is associated with serious complications after both cardiovascular and non-cardiac surgery [ 51 ]. Patients who require dialysis after surgery may have higher rates of mortality and kidney non-recovery [ 52 , 53 ].…”
Section: Predictors Of Renal Outcomesmentioning
confidence: 99%
“…AKI, especially AKI-D, is common and is associated with serious complications after both cardiovascular and non-cardiac surgery [ 51 ]. Patients who require dialysis after surgery may have higher rates of mortality and kidney non-recovery [ 52 , 53 ].…”
Section: Predictors Of Renal Outcomesmentioning
confidence: 99%
“…Факторы риска возникновения ОПП при трансплантации сердца были изучены множеством авторов. К предоперационным относятся предсуществующая почечная дисфункция, сахарный диабет, старший возраст как донора, так и реципиента, предшествующие трансплантации сердца; к интра-и послеоперационным: продолжительность ишемии трансплантата, операции и ИК, большая кровопотеря и объемные гемотрансфузии, механическая поддержка кровообращения, функциональная недостаточность сердечного трансплантата [69][70][71] [73][74][75].…”
Section: острое повреждение почек у реципиентов сердцаunclassified
“…A recent meta-analysis showed that incidences of AKI (according to KDIGO criteria) and AKI requiring renal replacement therapy (RRT) after HTX were 62.8% and 11.8%, respectively [3]. AKI post-HTX was associated with reduced long-term and 1-year patient survival [3,4]. In addition, AKI requiring RRT led to massive impairments regarding the patient's quality of life [4,5].…”
Section: Introductionmentioning
confidence: 99%